Advising in austerity: Reflections on challenging times for advice agencies - Kirwan, Samuel (Policy Press, 2017)
Available Open Access under CC-BY-NC licence. In a world dominated by austerity politics and policies, Advising in austerity provides a lively and thought-provoking account of the conditions, consequences and challenges of advice work in the UK, presenting a rare and rich view of the world of advice giving. Based on original research it examines how advisors negotiate the private troubles of those who come to Citizens Advice Bureaux (CAB) and construct ways forward. Exploring how advisors are trained, the strong contributor team reflect on the challenges facing Citizens Advice Bureaux in the future, where austerity will ensure that the need for advice services increase, while funding for such services declines.